Existence of equilibria of maps for pair of generalized games - DUBEY, ANIL KUMAR (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we prove some new common equilibrium existence theorems for generalized abstract economy pertaining to socio and techno economy with different types of correspondences.